2021
DOI: 10.1186/s13027-021-00353-8
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell‐free epstein–barr virus DNA levels and clinical features in Moroccan patients with nasopharyngeal carcinoma

Abstract: Background The identification of effective prognosis biomarkers for nasopharyngeal carcinoma (NPC) is crucial to improve treatment and patient outcomes. In the present study, we have attempted to evaluate the correlation between pre-treatment plasmatic Epstein-Barr virus (EBV) DNA load and the conventional prognostic factors in Moroccan patients with NPC. Methods The present study was conducted on 121 histologically confirmed NPC patients, recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…5 It is widely recognized that the TNM stage system and the Epstein-Barr virus (EBV) DNA play important roles in guiding NPC treatment, evaluation of curative efficacy, as well as prognosis prediction. 6 However, clinical outcomes significantly vary even among NPC patients with the same TNM stage and similar therapeutic regimens. 7 Moreover, EBV-DNA testing is a complex detection process, and is further characterized by the high cost of testing, and huge discrepancies in results, which consequently limit its promotion and practical application.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is widely recognized that the TNM stage system and the Epstein-Barr virus (EBV) DNA play important roles in guiding NPC treatment, evaluation of curative efficacy, as well as prognosis prediction. 6 However, clinical outcomes significantly vary even among NPC patients with the same TNM stage and similar therapeutic regimens. 7 Moreover, EBV-DNA testing is a complex detection process, and is further characterized by the high cost of testing, and huge discrepancies in results, which consequently limit its promotion and practical application.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous decade, many studies have shown that EBV DNA viral load is a sensitive and non-invasive biomarker for monitoring NPC. In the study by Gihbid et al, plasma EBV DNA levels were 4 times higher in patients over 30 years old [15], [16], [17], [18], [19], [20].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between pre-treatment EBV DNA load and conventional prognostic factors showed a significant association with patients’ age, tumour classification, lymph node status, metastatic status and overall cancer stage ( p = 0.01). The results of this study clearly demonstrated a high association between pre-treatment EBV DNA load, important classical prognostic factors (T, N, M and disease stage) of NPC and suggested that pre-treatment EBV DNA load can be a useful prognostic biomarker and improve the treatment of NPC [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gihbid et al[36] evaluated the correlation between pre-treatment plasma EBV DNA load and conventional prognostic factors in Moroccan NPC patients. Measuring the pre-treatment EBV plasma load, 90.9% of the patients had detectable EBV DNA, with a mean plasma viral load of 7,710 IU/mL.…”
mentioning
confidence: 99%